2018
DOI: 10.1111/cas.13791
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐inducible transgelin 2 selects epithelial‐to‐mesenchymal transition and γ‐radiation‐resistant subtypes by focal adhesion kinase‐associated insulin‐like growth factor 1 receptor activation in non‐small‐cell lung cancer cells

Abstract: Microenvironment, such as hypoxia common to cancer, plays a critical role in the epithelial‐to‐mesenchymal transition (EMT) program, which is a major route of cancer metastasis and confers γ‐radiation resistance to cells. Herein, we showed that transgelin 2 (TAGLN2), an actin‐binding protein, is significantly induced in hypoxic lung cancer cells and that Snail1 is simultaneously increased, which induces EMT by downregulating E‐cadherin expression. Forced TAGLN2 expression induced severe cell death; however, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…26 During tumor progression, TGF-β signaling was also found to be involved in the EMT that is critical in colorectal cancer, in which TGF-β activates RhoA and rho-associated protein kinase to induce actin polymerization. 15,21,27 In our study, we found TGF-βdependent activation of TAGLN expression is accompanied with decreased expression of E-cadherin, and increased levels of vimentin, fibronectin. It has been shown that TGF-β induced activation of TAGLN expression in tumor cells, especially in epithelial cells, can lead to a process of EMT, and TGF-β stimulated fibroblasts can lead to their transformation into myofibroblasts, which is important in tumor progression.…”
Section: Discussionsupporting
confidence: 54%
“…26 During tumor progression, TGF-β signaling was also found to be involved in the EMT that is critical in colorectal cancer, in which TGF-β activates RhoA and rho-associated protein kinase to induce actin polymerization. 15,21,27 In our study, we found TGF-βdependent activation of TAGLN expression is accompanied with decreased expression of E-cadherin, and increased levels of vimentin, fibronectin. It has been shown that TGF-β induced activation of TAGLN expression in tumor cells, especially in epithelial cells, can lead to a process of EMT, and TGF-β stimulated fibroblasts can lead to their transformation into myofibroblasts, which is important in tumor progression.…”
Section: Discussionsupporting
confidence: 54%
“…It is associated with stem cells, and acquisition of stem-like properties and quiescence [ 23 ]. In hypoxic cancer cells, Transgelin 2 (TAGLN2), an actin-binding protein, is induced, while in parallel, Snail1 is increased, leading to the induction of the EMT by downregulating the expression of E-cadherin [ 22 , 24 ]. The solute carrier family 1 (glial high affinity glutamate transporter), member 3 (SLC1A3), a glutamate transporter, mediates inter-niche stem cell activation [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a study on the tumor microenvironment of NSCLC demonstrated that the activation of the IGF1Rβ/PI3K/ AKT pathway by hypoxia could induce EMT, which might subsequently enhance radioresistance. 51 Consequently, we inferred that in NSCLC cells, radioresistance with enhanced DNA damage repair might be promoted by the miR-410-induced EMT process. However, to clearly understand the correlation between miR-410-induced EMT and radioresistance, a separate and effective tracing system is needed to monitor the EMT process because the EMT phenotype is reversible and transient.…”
Section: Discussionmentioning
confidence: 96%